Piloting, evaluating and modifying 'purposeful rounding' an evidenced based approach to nursing care: A private Catholic Health services approach to embedding evidence into practice. Issue 4 (December 2016) - Francis, K.L.; Steele, C.; Noonan, M.; Ryan, M.; Walter, Donna; Kurtsev, Andriy
Abstract : Background: Purposeful rounding' or 'intentional rounding' is a nursing led systematic evidenced-based nursing intervention designed to anticipate and address hospitalised patient needs (Fabry, 2015; Forde-Johnston, 2014; Harrington et al., 2013). 'Purposeful rounding' is reported to enhance patient safety by reducing risk, particularly risk related to 'falls', increase authentic regular interaction between nurses and patients and improve patient satisfaction with nursing care (Harrington et al., 2013; Hicks, 2015; McLeod &Telzlaff, 2015). This approach to care involves the judicious use of tools that assist nurses monitor patient wellbeing and limit preventable risk (Fabry, 2015). Objective: The introduction of 'purposeful rounding', as a technique to enhance health care outcomes was implemented at a St John of God acute care hospital in 2014–15 on a single ward as a pilot study and subsequently at a second St John of God acute care hospital in 2015–16 in all wards. Methods: A qualitative evaluation of the single ward pilot was completed following organisational human ethics approval that used interviews with nurses as the primary data collection technique. A mixed methods study design was conceptualised and approved by the organisations human ethics committee to evaluate the second hospitals adoption of 'purposeful rounding'. Data generation approaches included non-participant observation, interviews and focus groups with nursing staff, audits of documentation and patient satisfaction and staff surveys. The decision to use a broader range of data collection techniques was based on insights gained from the pilot that highlighted environmental, models of care, nursing skillmix, documentation and time management issues as critical factors influencing nurses' capacity to comply with the 'purposeful rounding' protocol. Results: There is no doubt that 'purposeful rounding' is useful. Our experience demonstrates patients feel safer when they see nursing staff regularly and that 'falls rates' reduce. Discussion/Conclusion: While the findings of our study reflect outcomes reported in the literature the contribution our research makes is the recognition that modifications to standardised practice protocols must be made for local conditions and these can't be realised until pilot studies are undertaken to isolate changes that are required to ensure 'best fit'. Translating evidence to practice must always be considerate of the local environment and resources.